Implementasi Akad Wakalah Bil Ujrah Pada Asuransi Jiwa Syariah - Warsidi; Isma Swadjaja; Sami Ullah Khan (Universitas Muhammadiyah Surabaya, 2026)
Abstract This study analyzes the implementation of the wakalah bil ujrah contract in Islamic life insurance products, focusing on the conformity of participant fund management with DSN-MUI Fatwa No. 52/DSN-MUI/III/2006. It applies a descriptive qualitative approach through a normative-empirical review of fatwas, insurance regulations, recent literature, and product documents such as sharia insurance application forms, policy summaries, policy provisions, benefit illustrations, and product information summaries. The findings indicate that wakalah bil ujrah positions participants as principals and the insurance company as an agent entitled to a fee for managing tabarru' funds and/or investment funds within agreed authority. Substantively, the practice can be considered sharia-compliant when it ensures clarity of contracting parties, delegated objects, amount and mechanism of ujrah, separation of participant and company funds, and avoidance of riba, gharar, and maisir. Nevertheless, fee transparency, participant literacy, and simplification of policy information remain critical areas to strengthen consumer protection and sharia compliance.